Pengaruh Pemberian Pakan Umbi Amorphophallus companulatus terhadap Persentase Karkas dan Non-Karkas Ayam Broiler - Luis, R; Mulyantini, N G A; Mulik, S E (PETERPAN (Jurnal Peternakan Terapan), 2025)
The suweg tuber (Amorphophallus companulatus) is a potential feed ingredient found in the East Nusa Tenggara (NTT) Province. However, suweg tuber (AC) contains anti-nutritional compounds such as oxalic acid, requiring pre-treatment before being fed to chickens. This study was designed to evaluate the effects of AC flour on slaughter weight, carcass weight, non-carcass weight, and abdominal fat accumulation. The study was conducted using a Completely Randomized Design (CRD) with four treatments, each replicated five times, totaling 20 experimental units. Each unit consisted of five broiler chickens, resulting in a total of 100 chickens. The treatments included AC00 (control, without AC), AC05 (5% AC), AC10 (10% AC), and AC15 (15% AC). The results of this study revealed that the inclusion of AC flour up to 15% could increase slaughter weight and carcass weight while reducing abdominal fat